Surface modification of poly (4, 4′-oxydiphenylene pyromellitimide) (Kapton) by alkali solution and its applications to atomic oxygen protective coating. (November 2016) - Shu, Ming; Li, Zhonghua; Man, Yanru; Liu, Kai; Liu, Huitao; Gao, Yuan
Highlights: The polyimide film treated by alkali solution under hydrothermal process is studied. The quality of SiOx coating depends on the surface modification of polyimide with alkali solution and silicon coupling agent. The SiOx coating can improve the resistance of polyimide to atomic oxygen erosion. Abstract: The hydrophobic surface of poly (4, 4′-oxydiphenylene pyromellitimide) (Kapton) is very difficult to combine strongly with hydrophilic SiOx coatings. In this paper, low concentration alkali solution is used to modify the Kapton surface under hydrothermal condition, combining with silicon coupling agents to improve the adhesion between SiOx coatings and Kapton matrix. SiOx coatings were prepared via sol-gel method and the samples were irradiated by atomic oxygen (AO). After AO exposure, the SiOx coatings became more uniform, without peeling off. The AO erosion yield value of coated Kapton was sharply down and the samples had good optical transparency.